Characteristics of Redestilled Dried Banana Leaves Liquid Smoke - Suroso, Erdi; Pratondo Utomo, Tanto; Al Rasyid, Harun; Fauzi, Aqshal (Jurnal Penelitian Pertanian Terapan, 2023)
Banana leaves belong to the waste products of the banana plant and are a potential source of liquid smoke due to their abundance, containing 10.85% cellulose, 19.95% hemicellulose and 18.21% lignin. Liquid smoke has many uses, including as an antibacterial agent and food preservative. The purpose of this study was to identify the characteristics of the liquid smoke from redistilled dried banana leaves. The process of making liquid smoke by pyrolysis, precipitation, distillation, and adsorption with activated zeolites. Liquid smoke is then physically observed for color and flavor, tested for compound content using GC-MS tests, and analyzed descriptively. The results showed that the liquid smoke from redistilled dried banana leaves had a mild taste and pale yellow color. was found to contain 13.09% area, carbonyls in 1.42% area, and no HPA compounds..